Computed tomography image fusion, Coaxial guidewire technique, Fast intraprocedural cortisol testing technique improves success rate and decreases radiation exposure, procedure time, and contrast use for adrenal vein sampling. Issue 9 (25th September 2021) - Liu, Zhenjie; He, Minzhi; Song, Xiaoxiao; Xu, Fangfang; Zhang, Binna; Chen, Bin; Yu, Peng; Zhou, Hanlei; Shan, Lizhen; Wang, Hongya; Gu, Zheng; Zhong, Shan; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Background: Adrenal vein sampling (AVS) is recommended for discriminating patients with unilateral primary aldosteronism from bilateral disease. However, it is a technically demanding procedure that is markedly underused. We developed a computed tomography image fusion, coaxial guidewire technique, fast intraprocedural cortisol testing (CCF) technique to improve AVS success rate, which combines CT image fusion, coaxial guidewire technique, and fast intraprocedural cortisol testing. Objective: To evaluate the effectiveness and safety of the AVS–CCF technique. Methods: We retrospectively evaluated 105 patients who undervent AVS from June 2016 to October 2020. There were 51 patients in the AVS–CCF group and 54 patients in the AVS group. We compared two groups with technical success rate, procedure time, radiation exposure, volume of contrast medium, and complications (adrenal vein rupture, dissection, infarction, or thrombosis; intraglandular or periadrenal hematoma; and contrast-induced nephropathy). Results: The technical success rate was higher for AVS–CCF than for AVS without CCF (98 vs. 83.3% for bilateral adrenal veins, P = 0.016). AVS–CCF was associated with a shorter procedure time (63.6 ± 24.6 vs. 94.8 ± 40.8 min, P < 0.001), shorter fluoroscopy time (15.6 ± 12.6 vs. 20.4 ± 15.0 min, P = 0.043), and lower contrast medium volume (25.10 ± 21.82 vs. 44.1 ± 31.0 ml, P < 0.001). There were no significant differences between groups with respect to the time for cannulating the left or right adrenal vein or the peak skin radiation dose. Adrenal vein rupture occurred in 14 patients and intraglandular hematoma in 1 patient. Conclusion: The CCF technique during AVS not only contributed to improved technical success rates but also associated with decreased procedure time, radiation exposure, and contrast medium volume.